2021
DOI: 10.1002/sctm.20-0489
|View full text |Cite
|
Sign up to set email alerts
|

Cell augmentation strategies for cardiac stem cell therapies

Abstract: Myocardial infarction (MI) has been the primary cause of death in developed countries, resulting in a major psychological and financial burden for society. Current treatments for acute MI are directed toward rapid restoration of perfusion to limit damage to the myocardium, rather than promoting tissue regeneration and subsequent contractile function recovery. Regenerative cell therapies (CTs), in particular those using multipotent stem cells (SCs), are in the spotlight for treatment post-MI.Unfortunately, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 155 publications
(290 reference statements)
0
2
0
Order By: Relevance
“…The previous static experiments revealed that all of the LNPs coated with proteins containing either SC3 or CshA in the N-terminal of the fusion proteins bind to C2C12 myoblasts and are internalized; however, an important aspect to consider for clinical relevance is the effect of flow-based shear stress. 47 Consequently, C2C12 myoblasts were allowed to adhere to flow channels (Ibidi μ-slides, 250,000 cells/channel) and subjected to shear stress (2 dyn) and monitored in real time using wide-field microscopy ( Figure S26 ). As under static conditions, colocalization of GFP and mCherry was observed only for 1:2 -LNPs ( Figure 5 a and Videos S1 and S2 ), and only GFP fluorescence was detected in cells treated with 1:3 -LNPs ( Figure 5 b and Videos S3 and S4 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The previous static experiments revealed that all of the LNPs coated with proteins containing either SC3 or CshA in the N-terminal of the fusion proteins bind to C2C12 myoblasts and are internalized; however, an important aspect to consider for clinical relevance is the effect of flow-based shear stress. 47 Consequently, C2C12 myoblasts were allowed to adhere to flow channels (Ibidi μ-slides, 250,000 cells/channel) and subjected to shear stress (2 dyn) and monitored in real time using wide-field microscopy ( Figure S26 ). As under static conditions, colocalization of GFP and mCherry was observed only for 1:2 -LNPs ( Figure 5 a and Videos S1 and S2 ), and only GFP fluorescence was detected in cells treated with 1:3 -LNPs ( Figure 5 b and Videos S3 and S4 ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…[317][318][319][320] Similarly, IHs loaded with miRNA, proangiogenic cytokines, growth factors, progenitor or stem cells are showing the capability of cardiac repair. [305,[321][322][323][324][325][326][327][328][329] Noninvasive magnetic resonance imaging (MRI) in combination with IHs is impactful in the fastest detection and repair (patient-specific) of infected cardiac tissues in cardiac arrest. [330][331][332][333][334] The target site, like the pericardial cavity, is considered to be best feasible toward the spatial retention of IHs.…”
Section: Applications Of Ihs For Wound Healing and Tissue Regenerationmentioning
confidence: 99%